biomedicalresearch 2019
DOI: 10.35841/biomedicalresearch.30-17-3359
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage of neisseria meningitidis among medical school students in Turkey.

Abstract: Objective: Neisseria meningitidis can colonise healthy human nasopharynx and is one of the most important etiologic agent of epidemic meningitis. The purpose of this study is to investigate the carriage rate, serogroup distribution and antibiotic resistance of Neisseria meningitidis in medical faculty students. Methods: Nasopharyngeal swab cultures were evaluated. Identification is made by convensional and semi-otomatised system. Serogroup analysis was performed with slide agglutination method. Minimum inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In two Nepalese studies on undergraduate medical students and healthcare workers, the S. pneumoniae carriage prevalence was 4% and 21%, respectively [ 20 , 39 ]. The pneumococcal carriage was also documented to be relatively low (3.2%) among medical students in a Turkish study [ 40 ]. A recent study among the indigenous community (70.7% adults) in Malaysian Borneo and another on adults in Indonesia recorded carriage prevalence of 10% and 11%, respectively [ 28 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two Nepalese studies on undergraduate medical students and healthcare workers, the S. pneumoniae carriage prevalence was 4% and 21%, respectively [ 20 , 39 ]. The pneumococcal carriage was also documented to be relatively low (3.2%) among medical students in a Turkish study [ 40 ]. A recent study among the indigenous community (70.7% adults) in Malaysian Borneo and another on adults in Indonesia recorded carriage prevalence of 10% and 11%, respectively [ 28 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For K. pneumoniae carriage, the prevalence in our study (11%) is identical to that documented among adults in an Indonesian study [ 41 ]. The Turkish study on medical students reported a significantly lower carriage prevalence of 0.8% [ 40 ], while the Borneo study reported a much higher prevalence of 30% among their target indigenous community in rural East Malaysia [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-seven samples (10.3%) were colonized with meningococcus; 28 cases (7.2%) were detected in the first sampling, at admission to the university and 49 cases (13.6%) were identified in the second sampling two months later; difference in the percentage was statistically significant (P = 0.008) [ 13 ]. In a study performed in Turkey between October 2013 and March 2015, Neisseria meningitidis was detected in 3 of the 475 nasopharyngeal swabs from asymptomatic medical students, revealing a prevalence of 0.6% [ 14 ]. Nasopharyngeal samples from 437 health care professionals at a tertiary university pediatric hospital in Australia were studied in 2020; colonization rate of meningococcus was 1.14 % [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a German study (2019) of asymptomatic meningococcal throat colonization in adults, married people were more likely to be colonized [ 20 ]. Living in a dormitory and having at least three roommates increases the rate of colonization [ 14 ]. In a study of pharyngeal carriage of meningococcus in Brazil (2014) the overall pharyngeal carriage of meningococcus in 11–19 years old children was 4.9% and it was higher when mother was the only smoker in the home [ 21 ].Tobacco use and passive smoking in the last 30 days had a significant relationship with pharyngeal colonization in students, as reported from a study done in the United States in 2015 [ 6 ] The rate of pharyngeal colonization with meningococcus in Hajj pilgrims has decreased due to vaccination and ciprofloxacin consumption before leaving for the trip to Mecca [ 22 ].…”
Section: Discussionmentioning
confidence: 99%